Chromatographic NMR Spectroscopy with Hollow Silica Spheres. (25th January 2016) - González‐García, Tania; Margola, Tommaso; Silvagni, Adriano; Mancin, Fabrizio; Rastrelli, Federico
Abstract: The use of micrometric hollow silica spheres is described as a strategy to reduce magnetic field inhomogeneities in the context of NMR chromatography. When employed as a stationary phase, hollow silica microspheres allow the use of common solution‐state NMR instruments to measure the diffusion coefficient perturbation induced by the interaction of the analytes with the silica surface.